Pemberdayaan Masyarakat Pekebun Kampung Wasur Melalui Edukasi Dan Pelatihan Pembuatan Pupuk Organik Cair Dari Sampah Rumah Tangga - Ineke Nursih Widyantari; Stanly HD Loppies; Gerzon Jokomen Maulany (Altifani Journal: International Journal of Community Engagement, 2025)
Wasur Village, Merauke District, Merauke Regency, is a local village where most residents practice gardening to meet their family's needs, whether for personal consumption or for sale. This community service program aims to provide education and training to the community in Wasur Village. Hence, they know how to make liquid organic fertilizer from household organic waste. The methods used in this community service program include educating participants through counseling, providing technical guidance on making liquid organic fertilizer (POC), and educating them on how to package and market the POC. The results of this activity showed that the community service program's first and second phases ran smoothly due to the support of residents and village officials. This community service program has transformed organic waste, which would usually be discarded, into something more useful after further processing, and can become an alternative fertilizer and increase family income.